Efectividad de la función disciplinaria ejercida por la Procuraduría General de la Nación frente a los servidores públicos de elección popular (2018)
The purpose of this document is to carry out a brief study of the effectiveness of the disciplinary function exercised by the Attorney General's Office vis-à-vis public servants of popular election, taking into account the regulatory framework, in the light of the Sole Disciplinary Code, the Jurisprudence of the Supreme Court of Justice and the Council of State, if the effectiveness is consistent with the Disciplinary Faculty of the Attorney General of the Nation against the investigations and imposition of sanctions to the inappropriate behavior of public servants of popular election. The aim is to clarify whether the essential purposes of the State are being guaranteed through the monitoring and obligation granted to the Public Ministry, taking into account the legal and constitutional obligations of public servants and the effectiveness of the sanctioning consequences of violating the law or the Constitution. Politics of Colombia.